Improved Torque Control Performance in Direct Torque Control using Optimal Switching Vectors - Muhd Zharif Rifqi Zuber Ahmadi; Auzani Jidin; Maaspaliza Azri; Khairi Rahim; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents the significant improvement of Direct Torque Control (DTC) of 3-phases induction machine using a Cascaded H-Bidge Multilevel Inverter (CHMI). The largest torque ripple and variable switching frequency are known as the major problem founded in DTC of induction motor. As a result, it can diminish the performance induction motor control. Therefore, the conventional 2-level inverter has been replaced with CHMI the in order to increase the performance of the motor either in dynamic or steady-state condition. By using the multilevel inverter, it can produce a more selection of the voltage vectors. Besides that, it can minimize the torque ripple output as well as increase the efficiency by reducing the switching frequency of the inverter. The simulation model of the proposed method has been developed and tested by using Matlab software. Its improvements were also verified via experimental results.